The use of impression management practices in the chairman’s statements in South African annual reports - Yaeesh Yasseen; Waheeda Mohamed; Mahdiyyah Moola-Yasseen (Communicare)
Impression management is the study of how individuals present themselves to be perceived favourably. Using agency theory, this article investigates impression management practices, influenced by the company’s underlying performance, that may be present in the chairman’s statements in annual or integrated reports of Johannesburg Stock Exchange listed companies in South Africa. This research uses content analysis and specifically focuses on the identification and measurement of three pre-determined textual characteristics referenced in these chairman’s statements. There is reasonable evidence to suggest that management employs impression management strategies that are dependent on the level of a company’s performance. In addition, while variability in readability was not found to be a strategy used to manage impressions, the overall readability of the chairman’s report was found to be relatively difficult and this, in turn, may affect the ability of stakeholders to benefit from the information it contains. This study is limited to the analysis of a single section of narrative reporting (the chairman’s statement) and, as such, does not consider any impression management practices that may be present in the rest of the annual or integrated report as well as in other communications between stakeholders and the company in question. It is anticipated that the results will be of importance to professional accountancy bodies, users and preparers considering the negative perception of the accounting profession owing to recent scandals. This is also one of the first studies to explore the use of impression management practices in South Africa and the linguistic variation employed in management commentary within a South African context, thereby contributing to the readability of the chairman’s statements.